Slippery Knowledge: Ignorance, Ecologies, and Environment in Endometriosis Framing. - Ford, Andrea (Medical Anthropology Quarterly, 2025)
Despite a growing body of literature linking environmental toxins and endometriosis, environmental issues make only occasional appearances in public, patient, and specialist conversations about endometriosis. These conversations may hover at the edges of public discourse, but do not gain traction. Based on ethnographic work in the United Kingdom, this article develops the concept of "slippery" knowledge as that which evades action. Ignorance of environmental or ecological etiologies is less a dearth of information than a dearth of possibilities for action. This article elaborates two ways of conceiving of environmental or ecological disease: the exposure model predicated on harmful external factors "getting in" to damage individuals or communities and the embodied ecologies model, which posits inevitable and ongoing mutual imbrication among living and non‐living entities. Knowledge regarding endometriosis is "slippery" in both models. Whether knowledge seems actionable or not is inextricable from deep‐seated power dynamics related to colonialism, gender, and race, which perpetuate ways of knowing (and acting) on endometriosis that are troubling and troublingly durable.